PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PANEN DI PT. DEWATA SAWIT NUSANTARA - Oki Ristanto; Muh Yamin; Mujibu Rahman; Daryono; Yuanita (Politeknik Pertanian Negeri Samarinda, 2019)
This research is motivated by how the level of work environment influences the satisfaction of harvest employees, it needs to be understood that the expected satisfaction of an employee is not easily influenced by various factors of compensation, motivation, work environment and other factors, therefore the purpose of this study is to know the possibility of environmental influences on the job satisfaction of harvest employees. This research is a case study at PT. dewata palm archipelago, east Kalimantan. The population in this study were harvest employees, totaling 40 respondents. Data collection method is a questionnaire. The sampling technique uses cluster sampling. Data analysis techniques using simple linear regression equation models and using the t test to analyze the closeness of the relationship of individual variables, while testing the instrument using the test of validity and reliability The results showed there was a significant influence of the work environment on employee job satisfaction value of Sig = 0.39 <0, 05 and the value of t table shows there is a direction of the positive influence of the physical work environment on employee job satisfaction (t count = 3.335> t table = 2.021).